Efficacy of Regenerative Medicine for Alveolar Cleft Reconstruction: A Systematic Review and Meta-analysis - Motamedian, Saeed R.; Mohaghegh, Sadra; Lakmazaheri, Ehsan; Ahmadi, Nima; Kouhestani, Farnaz (Current Stem Cell Research & Therapy, 2022)
Objective: The objective of this study is to analyze the efficacy and complications of regenerative medicine compared to autogenous bone graft for alveolar cleft reconstruction. Method: Electronic search was done through PubMed, Scopus, Embase and Cochrane databases for the studies published until May 2021. No limitations were considered for the type of the included studies. The risk of bias (ROB) of the studies was assessed using the Cochrane Collaborations and NIH quality assessment tool. Meta-analyses were performed to assess the difference in the amount of bone formation and rate of complications. Grading of Recommendations, Assessment, Development and Evaluation (GRADE) was used for analyzing the level of the evidence. Results: Among a total of 42 included studies, 21 studies used growth factors, 16 studies delivered cells, and five studies used biomaterials for bone regeneration of the alveolar cleft. Results showed no significant difference in the amount of bone formation between bone morphogenic protein-2 and iliac graft treated patients after six months (P = 0.44) and 12 months (P = 0.17) follow-up. Besides, higher swelling (OR=9.46, P < 0.01) and less infection (OR=0.19, P = 0.01) were observed in BMP treated patients. Using stem cells can reduce the post-treatment pain (OR=0.04, P = 0.01), but it has no significant impact on other complications (P > 0.05). Using tissue engineering methods reduced the operation time (SD=1.06, P < 0.01). GRADE assessment showed that results regarding the amount of bone formation volume after six and 12 months have low level of evidence. Conclusion: Tissue engineering methods can provide a comparable amount of bone formation to the autogenous graft and reduce some of the complications, operation time and hospitalization duration.
Keywords: stem cells